Aktivitas Komunikasi Organisasi dan Kinerja Pendamping dalam Program Gernas Kakao di Kabupaten Polewali Mandar - Nurul Mukhlishah; Amiruddin Saleh; Dwi Sadono (Jurnal Komunikasi Pembangunan, 2014)
AbstractGernas  programs  utilize  partners  to  deliver  innovative  messages  and  informations  that  able to empower  thefarmers.  However, in the process of mentoring  it  is not  neglecting the competences of the are performance of the partners.  One effort which can control the performance of the partners is through communication.  Communication serves as a main tool for success or failure organization in conjunction with the enviro nment duty. The objectives of this study is  to  analyze the correlation of organizational communication with the performance  of the partners.  This research was conducted at Polewali Mandar using survey method. The number of respondents were 33 people based on  census  method and using  correlational  analysis  to  process the results.  Results of the study  that the  frequency  of organizational  communication significantly  correlated to quality  of work, a  good  cooperation of the partners, and knowledge about job, and the level of use a communication channels significantly correlated  to quality and quantity of work, a good cooperation of the partners, and knowledge about job.Key words: Organizational communication, performance, program’s partner